(Perservation of salted Press-Boiled Milk Fish (Chanos chanos) by Packaging Method) - Dwi Sutrisniati; Aan Yulistia; Juli Astuti (Warta Industri Hasil Pertanian, 1987)
A study on the preservation of salted press-boiled ("pindang") milk fresh (Chanos chanos) by packaging method had been carried out. "Pindang" was prepared eith prepared with or without the addition of potasium sorbate or potasium sorbate. The products were packaged with or without vacuum in the polycello film and stored at room temperature. Observation was done on moisture content, number of peroxide, trimethhylamine, total Bacterial Count (TPC) and organoleptic test. The result showed that up to 8 week of storage, all of the teratments were acceptable. The use of potasium sorbate and sodium eryhorbate combimed with vacuum packaging, showed the best performance.